2008
DOI: 10.1021/bi701360j
|View full text |Cite
|
Sign up to set email alerts
|

The N-Terminal Basic Domain of the HIV-1 Matrix Protein Does Not Contain a Conventional Nuclear Localization Sequence But Is Required for DNA Binding and Protein Self-Association

Abstract: The HIV p17 or matrix (MA) protein has long been implicated in the process of nuclear import of the HIV genome and thus the ability of the virus to infect nondividing cells such as macrophages. While it has been demonstrated that MA is not absolutely required for this process, debate continues to surround the subcellular targeting properties of MA and its potential contribution to nuclear import of the HIV cDNA. Through the use of in vitro techniques we have determined that, despite the ability of MA to intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 52 publications
(81 reference statements)
4
45
0
Order By: Relevance
“…Furthermore, binding of membranes by MA and association of cytoplasmic RNAs and proteins with multiple Gag domains should additionally prevent nuclear entry. A saturation or failure of these cytoplasmic retention mechanisms due to large amounts of intracellular Gag/Gag-Pol after transient transfection could sequester Gag in the nucleus potentially by the ability of MA to bind unspecifically to DNA and RNA (29). Our observation that Gag does not enhance the export of nuclear gRNA for subsequent translation and encapsidation is consistent with the RNA packaging model (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, binding of membranes by MA and association of cytoplasmic RNAs and proteins with multiple Gag domains should additionally prevent nuclear entry. A saturation or failure of these cytoplasmic retention mechanisms due to large amounts of intracellular Gag/Gag-Pol after transient transfection could sequester Gag in the nucleus potentially by the ability of MA to bind unspecifically to DNA and RNA (29). Our observation that Gag does not enhance the export of nuclear gRNA for subsequent translation and encapsidation is consistent with the RNA packaging model (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, expression of gag from the codon-optimized expression plasmid Gag opt or expression of almost the full repertoire of HIV-1 proteins and RNAs following transfection of the proviral construct HXB2⌬env⌬nefCAT led to similar results. The conclusion that Gag lacks a Crm1-dependent NES is strengthened by the fact that in similar LMB inhibition assays MA did not accumulate in the nuclei of transfected cells either (16,29).…”
Section: Discussionmentioning
confidence: 95%
“…The HIV-1 MA domain was reported previously to have two NLSs (5,21) and one NES (13), but multiple subsequent reports have shown that HIV-1 MA-GFP is excluded from the nucleus (2,10) and that it does not contain a conventional NLS (15,22). Two studies in the past year confirmed that HIV-1 Gag lacks a CRM1-dependent nuclear export signal (2,18).…”
Section: Discussionmentioning
confidence: 96%
“…This effect of the 74LR change may be accounted for by one of several mechanisms in which MA affects viral infectivity. First, although involvement of MA in nuclear import of preintegration complexes is unsubstantiated (reviewed in reference 31), several reports showed that alteration of MA residues modulates other steps of the postentry process (5,8,10,16,31,32,37,38,45). For example, substitutions of Leu20 in MA impair viral DNA synthesis early postentry (37,38).…”
Section: Vol 85 2011mentioning
confidence: 99%